2020
DOI: 10.1080/13676261.2020.1757632
|View full text |Cite
|
Sign up to set email alerts
|

‘You can’t just be a Muslim in outer space’: young people making sense of religion at local places in the city

Abstract: View related articles View Crossmark data Citing articles: 1 View citing articles 'You can't just be a Muslim in outer space': young people making sense of religion at local places in the city

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Although the number of mosques is increasing, their role seems to be limited to certain acts of worship, such as for Islamic lecturers, prayer, dhikr, and Quran reading (Hamid et al, 2019;Putung@Abd.Mutalib & Ag.Basir, 2012;Suhardi et al, 2022), which are mainly attended by veterans (Ashaari & Firdaus, 2018;Darus et al, 2017;Mansor et al, 2011;Yussoff & Shaharuddin, 2020), and the younger generation seems to be turning away from the mosque (Fazaqa, 2009;Ibrahim et al, 2020;Kapinga & Van Hoven, 2021). The absence of young generations from the mosque is not only observed in Malaysia, but also in other parts of the world (Fazaqa, 2009;Kapinga & Van Hoven, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the number of mosques is increasing, their role seems to be limited to certain acts of worship, such as for Islamic lecturers, prayer, dhikr, and Quran reading (Hamid et al, 2019;Putung@Abd.Mutalib & Ag.Basir, 2012;Suhardi et al, 2022), which are mainly attended by veterans (Ashaari & Firdaus, 2018;Darus et al, 2017;Mansor et al, 2011;Yussoff & Shaharuddin, 2020), and the younger generation seems to be turning away from the mosque (Fazaqa, 2009;Ibrahim et al, 2020;Kapinga & Van Hoven, 2021). The absence of young generations from the mosque is not only observed in Malaysia, but also in other parts of the world (Fazaqa, 2009;Kapinga & Van Hoven, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although the number of mosques is increasing, their role seems to be limited to certain acts of worship, such as for Islamic lecturers, prayer, dhikr, and Quran reading (Hamid et al, 2019;Putung@Abd.Mutalib & Ag.Basir, 2012;Suhardi et al, 2022), which are mainly attended by veterans (Ashaari & Firdaus, 2018;Darus et al, 2017;Mansor et al, 2011;Yussoff & Shaharuddin, 2020), and the younger generation seems to be turning away from the mosque (Fazaqa, 2009;Ibrahim et al, 2020;Kapinga & Van Hoven, 2021). The absence of young generations from the mosque is not only observed in Malaysia, but also in other parts of the world (Fazaqa, 2009;Kapinga & Van Hoven, 2021). As published in the Journal of Youth Studies, in an effort to show how young people make sense of religion on their journey to adulthood, Kapinga & Van Hoven (2021) found that almost all respondents in Metro Vancouver agreed that young people largely stay away from the mosque, even though the place serves some of their important functions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These ideas are reflected in the reinventing self during through rituals. The practices can be seen as lived religion that is affected by the everyday context (Kapinga & van Hoven, 2020). Other studies define it is a continuous learning process, along with its practices (Langellier, 2010).…”
Section: Muslim Religious Identitymentioning
confidence: 99%
“…My PhD project aims to understand the interaction between experiences in everyday urban spaces and how religion is explored and negotiated by young Muslims while moving from youth to adulthood (e.g. Kapinga & van Hoven, 2020). Two cases are involved in the project: Vancouver (Canada) and Groningen (The Netherlands).…”
Section: Researching Religionmentioning
confidence: 99%